Control of LDL Uptake in Human Cells by Targeting the LDLR Regulatory Long Non-coding RNA BM450697 - Roslyn M. Ray; Anders Højgaard Hansen; Sofie Slott; Maria Taskova; Kira Astakhova; Kevin V. Morris (Elsevier, 2019)
Hypercholesterolemia is a condition that is characterized by very high levels of cholesterol in the blood and is a major correlating factor with heart disease. Indeed, high levels of the low-density lipoprotein (LDL) have been causally linked to the development of atherosclerotic cardiovascular disease (ASCVD). A method to specifically reduce cholesterol in the blood in a long-term, stable manner could prove therapeutically relevant. Cholesterol is removed from the blood by the LDL receptor (LDLR) in the liver. Others and we have discovered that a long non-coding RNA (lncRNA; BM450697) functions as an endogenous epigenetic regulator of LDLR and that the repression of this lncRNA by the action of small interfering RNAs (siRNAs) results in the activation of LDLR. We found here, through the interrogation of two siRNAs that can target this lncRNA, both in a transcriptional and post-transcriptional manner, that BM450697 functions as a local scaffold for modulating LDLR transcription. Moreover, we found that conjugation of α-N-acetylgalactosamine (GalNAc) with two lncRNA-directed siRNAs allows for direct liver cell targeting of this lncRNA and functional enhanced uptake of cholesterol. Collectively, these data suggest that targeting the BM450697 lncRNA regulator of LDLR may result in a more specific, long-term, targeted approach to regulating cholesterol in the blood. Keywords: LDL, LDLR, lncRNA, cholesterol, transcriptional gene silencing, Galnac, siRNA, hypercholesterolemia